Cinderella, or, The little glass slipper - Perrault, Charles, 1628-1703.; Brown, Marcia (New York : Aladdin Books, 1988)
Brown's illustrated translation of Perrault's tale in which Cinderella leaves behind a glass slipper in her haste to flee the palace before the fairy godmother's magic loses effect won the 1955 Caldecott medal.
Translation of: Cendrillon.
School Library Journal
Caldecott 1955 Medal Winner
School Library Media Quarterly (A.A.A.L.)
3.0
K-3
Keywords: Fairy tales; Folklore -- France; Caldecott 1955 Medal Winner; Fairy tales; Folklore -- France; Caldecott 1955 Medal Winner